Successful Endovascular Management of Intra-meatal Anterior Inferior Cerebellar Artery–Posterior Inferior Cerebellar Artery Variant Aneurysm - Bohra, Vikram; DeSouza, Romnesh; Huded, Vikram (Journal of Clinical Interventional Radiology ISVIR, 2018)
Anterior inferior cerebellar artery–posterior inferior cerebellar artery (AICA-PICA) variant or common trunk is seen frequently in vertebral angiograms as PICA is found to be hypoplastic or absent in approximately 20 to 25% of patients. There have been very few case reports of aneurysm arising in AICA-PICA variant. Intrameatal AICA aneurysms are also rare, with no reports involving AICA-PICA variant till date. Neurosurgical approach and clipping have been proposed as first-line treatment option for intrameatal AICA aneurysms. The authors report a case of a young woman presenting with subarachnoid hemorrhage, found to have a right AICA-PICA variant aneurysm in intrameatal location. The patient underwent coiling with parent vessel occlusion after an unsuccessful attempt at surgical management of the same. She recovered without any postprocedure complication. This case report highlights the fact that endovascular approach can be used to manage distal AICA/AICA-PICA variant or intrameatal aneurysm with added advantage of avoiding the postprocedure complications associated with surgical management of the same.
Keywords: AICA-PICA variant; intrameatal aneurysm; coiling